HUBUNGAN KUALITAS BIMBINGAN INSTRUKTUR CLINICAL SKILL LAB (CSL) DENGAN TINGKAT KEPUASAN MAHASISWA DI FAKULTAS KEDOKTERAN UNIVERSITAS PATTIMURA - Siahaya, Christo Imanuel; Huwae, Laura Bianca Sylvia; Hataul, Is Ikhsan; Saija, Alessandra; Noija, Stazia; Tentua, Vebiyanti (PAMERI, 2024)
The educational method applied in the Clinical Skill Lab (CSL) is a student-centered, integrated, problem-based, independent, and multi-professional learning approach. There are many limitations obtained in the CSL process that impact students' satisfaction level with the instructor as a guide for students to deepen a skill. This study aims to determine the relationship between the quality of CSL instructor guidance and student satisfaction level at the Faculty of Medicine, Pattimura University. This study uses a quantitative analytical method with a cross-sectional research design. The sample of this study is students of the 2019, 2020, and 2021 batches, totaling 525 respondents. Data collection uses a questionnaire that is shared with students through Google Forms. The results of the univariate analysis showed that the quality of CSL instructor guidance was mainly in the good category (36.2%), and the level of student satisfaction was in the very satisfied category (52.8%). The bivariate analysis results showed a significant relationship between the quality of guidance provided by CSL instructors and the level of student satisfaction at the Faculty of Medicine, Pattimura University of Ambon (p<0.001). It can be concluded that there is a relationship between the level of quality of guidance provided by CSL instructors and the level of student satisfaction at the Faculty of Medicine, Pattimura University of Ambon.